1989
DOI: 10.1111/j.1468-2958.1989.tb00206.x
|View full text |Cite
|
Sign up to set email alerts
|

When a Lot of Knowledge Is a Dangerous Thing The Debilitating Effects of Plan Complexity on Verbal Fluency

Abstract: Three experiments examined the relationships among plan complexity, access to planned actions, and verbalfluency while pursuinga persuasiongoal. Consistent with theoretical expectations, complex planners were less fluent than less complex planners under high access conditions. Persons whose access was raised were less fluent than those whose access was not raised. A second experiment showed that reducedfluency was not induced by lowering of self-confidence. The third experiment replicated thefindings of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 22 publications
(20 reference statements)
1
55
0
1
Order By: Relevance
“…These gains, however, were offset by an undue reliance on the support system causing pilots to miss salient changes in the performance context. Along similar lines, C. R. Berger et al (1989) found that having others ask questions about plans increased plan length and complexity but, by the same token, decreased execution fluency. Thus, the effects of support systems on planning may be quite complex, requiring the tailoring of support interventions to the unique issues impinging on performance within the setting at hand.…”
Section: What Situational Factors Are Associated With Successful Planmentioning
confidence: 84%
See 1 more Smart Citation
“…These gains, however, were offset by an undue reliance on the support system causing pilots to miss salient changes in the performance context. Along similar lines, C. R. Berger et al (1989) found that having others ask questions about plans increased plan length and complexity but, by the same token, decreased execution fluency. Thus, the effects of support systems on planning may be quite complex, requiring the tailoring of support interventions to the unique issues impinging on performance within the setting at hand.…”
Section: What Situational Factors Are Associated With Successful Planmentioning
confidence: 84%
“…Difficulty and complexity, however, may exert a number of somewhat more complex effects on planning. For example, C. R. Berger et al (1989) found that the need for more complex plans led to loss in terms of both access to key plan components and the fluency with which a plan (in this study, communication plans) could be executed. Along similar lines, one might expect that complexity would make identification of relevant causes, management of contingencies, and ordering of activities more demanding and time consuming.…”
Section: What Situational Factors Are Associated With Successful Planmentioning
confidence: 93%
“…Hjelmquist, 1991;Hjelmquist & Gidlund, 1984;Kendon, 1987;Levelt, 1989), and communication researchers have recognized the important role played by plans and planning in guiding communicative action (Berger, 1988a(Berger, , 1988bBerger, Karol, & Jordan, 1989;Daly, Weber, Vangelisti, Maxwell, & Neel, 1989;Waldron, 1990;Waldron, Cegala, Sharkey, & Teboul, 1990;Wilson, 1990). In Waldron's (1990) study of 2,273 thoughts generated by subjects during reviews of videotapes of their interactions, 27% of the thoughts had to do with planned actions for reaching interaction goals, while an additional 17% were concerned with the goals themselves.…”
Section: Planning Sources Planning Difficulty and Verbal Fluency Chamentioning
confidence: 94%
“…According to Infante (1980), a verbal plan consists of "what an individual intends to say in a specific situation or in a general situation" (p. 3). Clearly, in recent years communication scholars have become increasingly attentive to features of verbal plans in general (Berger, 1987;Berger & Bell, 1988;Berger & DiBattista, 1993;Berger, Karol, & Jordan, 1989;Plax, Beatty, & Feingold, 1991). Within the context of the present study, however, the conceptualization of fathers' plans includes both verbal and nonverbal components.…”
mentioning
confidence: 85%